2016
DOI: 10.1152/physiolgenomics.00109.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sports genetics moving forward: lessons learned from medical research

Abstract: Sports genetics can take advantage of lessons learned from human disease genetics. By righting past mistakes and increasing scientific rigor, we can magnify the breadth and depth of knowledge in the field. We present an outline of challenges facing sports genetics in the light of experiences from medical research. Sports performance is complex, resulting from a combination of a wide variety of different traits and attributes. Improving sports genetics will foremost require analyses based on detailed phenotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 72 publications
0
49
0
4
Order By: Relevance
“…We recently conducted a meta-analysis of candidate gene association studies examining the BP response to acute (i.e., PEH) and chronic (i.e., training) aerobic exercise and found that Angiotensiogen (AGT) rs699 emerged as the only promising variant to explore further (Bruneau et al 2015). This finding substantiates a major concern of candidate gene association studies that examine the response of health-related phenotypes to exercise; that is, most statistically significant findings fail to replicate due to a variety of factors that include the lack of standardized protocols, statistical adjustments for multiple comparisons, and adequately powered samples (Bouchard 2011;Bouchard et al 2012;Ash et al 2013a;Bruneau et al 2015;Mattsson et al 2016).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We recently conducted a meta-analysis of candidate gene association studies examining the BP response to acute (i.e., PEH) and chronic (i.e., training) aerobic exercise and found that Angiotensiogen (AGT) rs699 emerged as the only promising variant to explore further (Bruneau et al 2015). This finding substantiates a major concern of candidate gene association studies that examine the response of health-related phenotypes to exercise; that is, most statistically significant findings fail to replicate due to a variety of factors that include the lack of standardized protocols, statistical adjustments for multiple comparisons, and adequately powered samples (Bouchard 2011;Bouchard et al 2012;Ash et al 2013a;Bruneau et al 2015;Mattsson et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…In addition, we instituted methodological strategies to increase the statistical power to detect renal genotype-BP associations should they exist (Bouchard 2011;Ash et al 2013a;Bruneau et al 2015;Mattsson et al 2016). These strategies included a repeated measure design among the same individuals that increased the number of observations per subject by 19 hourly time points, a focused inquiry of polymorphisms with a prioritized panel of genes that reduced the search space within the genome, performing high throughput exon sequencing to focus on functional regions of the gene, and inclusion of the same standardized protocols and methods in our discovery phase and replication studies.…”
Section: Discussionmentioning
confidence: 99%
“…ACTN3 and ACE ) polymorphisms have been associated with an acceptable level of replication with endurance or power athletic performance, and none of these associations are strong enough to predict elite sports performance or trainability [14, 23, 24]. Currently, there is lack of scientific evidence supporting the predictive values of genetic tests (direct-to-consumer) for prescription of exercise training programmes, or for that matter, talent identification.…”
Section: Commentmentioning
confidence: 99%
“…To improve the effectiveness of sports genetics primarily will require analysis based on a detailed full [17,18].…”
Section: Regional Aspects Of Sports Medicinementioning
confidence: 99%
“…Angiotensin-converting enzyme gene (ACE) which had concluded that one of the polymorphic alleles of ACE gene is allele-I provides tolerance, and allele-D -speed-power qualities of athlete, on the basis of higher frequency of alleles in athletes, successful in their respective sports in relation to the control group [17]. However, in the future, a number of authors will find no differences in the frequency of occurrence of genotypes in athletes and people who are not involved in sports [18,19]. Nevertheless, differences will be appeared in the analysis of the study in athletes' genotypes, specializing in several sport fields [20].…”
mentioning
confidence: 99%